Regulation of the pAD1-encoded sex pheromone response in Enterococcus faecalis: expression of the positive regulator TraE1. - Tanimoto, K (1993)
pAD1 is a conjugative, 60-kb, hemolysin-bacteriocin plasmid in Enterococcus faecalis that encodes a mating response to a small peptide sex pheromone, cAD1, secreted by potential recipient bacteria. The response is regulated by a cluster of genes that includes a positive regulatory determinant, traE1, able to activate key structural genes involved in the conjugative process. A negative regulatory determinant, traA, affects the expression of traE1 and is sensitive to the pheromone signal. Between the two determinants is a gene, iad, which encodes a small peptide, iAD1, a competitive inhibitor of cAD1. The determinants (traE1-iad-traA) are oriented such that iad and traE1 are transcribed in the same direction, opposite that of traA. Transcription of iad and traA starts between these determinants and moves outward in each case. A recent report from our laboratory, dealing with transcriptional fusions in the traE1-iad region (L. T. Pontius and D. B. Clewell, J. Bacteriol. 174:3152-3160, 1992), indicated that traE1 expression may be dependent on transcriptional read-through of a terminator(s) between iad and traE1. The present report provides direct analyses of relevant RNA species before and during induction and shows that indeed transcriptional read-through from iad is important in the initial expression of traE1. However, the data show that once traE1 is activated, it can then be expressed independently, probably because of TraE1 activating its own promoter. This view is also supported by genetic complementation studies. In addition, DNA binding studies with TraA showed that the protein binds to the promoter of iad. Binding of TraA to the region between iad and traE1 could not be detected; however, the involvement of TraA in influencing transcription termination in this region is still not ruled out, since additional factors could be involved. A model for the regulation of the pheromone response is presented.